OBSTACLES TO THE IMPLEMENTATION OF SUPREME COURT REGULATION (PERMA) NUMBER 7 OF 2022 ON ELECTRONIC CASE ADMINISTRATION AND ELECTRONIC COURT PROCEEDINGS IN DIVORCE CASES AT THE SLAWI RELIGIOUS COURT, TEGAL REGENCY - Aziz Mahmud Idris; Sanusi; Soesi Idayanti (RADJA PUBLIKA, 2026)
The Supreme Court has issued a regulation concerning electronic case administration, namely Supreme Court Regulation of the Republic of Indonesia (PERMA RI) Number 7 of 2022 on Electronic Case Administration in Courts. The purpose of this regulation is stipulated in Article 2 of Supreme Court Regulation of the Republic of Indonesia Number 7 of 2022 on Electronic Case Administration in Courts, namely to support the realization of professional, transparent, accountable, effective, efficient, and modern case administration. (PERMA, 2022). In accordance with Supreme Court Regulation Number 7 of 2022 concerning electronic case administration in courts, the scope of the e-Court application generally includes: (1) Online Case Registration (e-Filing), (2) Online Advance Court Fee Payment (e-Payment), (3) Electronic Summons (e-Summons), and (4) Electronic Court Proceedings (e-Litigation). (PERMA, 2021). This study aims to identify the obstacles to the implementation of e-litigation proceedings in divorce cases at the Slawi Religious Court, Tegal Regency. This research employs library research with an empirical juridical approach and qualitative analysis methods, with the Slawi Religious Court Class IA serving as the research object. The main obstacles to the implementation of Supreme Court Regulation Number 7 of 2022 at the Slawi Religious Court include the public's low level of technological literacy (digital divide), unstable internet infrastructure, and difficulties in verifying the defendant's electronic domicile. Other obstacles include limited public understanding of electronic fee-waiver (prodeo) services and technical challenges encountered during virtual court proceedings. Kata Kunci : Case Obstacles, Electronic Court Proceedings, Effectiveness and Efficiency, Divorce Cases.